Does the Ohio River Flow All the Way to New Orleans?1. (20th February 2018) - Brooks, Robert P.; Limpisathian, P. William; Gould, Timothy; Mazurczyk, Tara; Sava, Elena; Mitsch, William J.
Abstract: Rivers were among the first geographical features in the United States (U.S.) to receive official names, often initially stemming from Native American heritage. Today river titles portray both cultural and physical origins. These naming conventions provide a descriptive connotation driven by social perceptions. At present, most people accept that the Mississippi River is the largest river and "mother river" in the U.S. Our investigation explored this river's prominence in the U.S. by identifying and comparing various hydrologic, biological, and cultural metrics. We used six variables to determine the magnitude of river importance: 30‐year average discharge, length, drainage area, fish richness, fish endemism, and river‐specific song lyrics. The Mississippi, Missouri, and Ohio River Basins were evaluated using data from nine selected U.S. Geological Survey gaging stations and ranked using the six metrics. Using an average for the rankings across the three rivers, the Ohio is ranked highest for three individual metrics (discharge, fish richness, and fish endemism), and highest across the average for all six metrics, and for an average of five metrics, including hydrology and biodiversity metrics. Thus, our results suggest that the Ohio River could be considered the most prominent river in the U.S. and that the river itself should have the same name (Ohio or Mississippi) from New Orleans to at least Pittsburgh, Pennsylvania.